The role of ribavirin in the therapy of Crimean-Congo hemorrhagic fever: early use is promising - (:unkn) unknown (SPRINGER, 2009)
Crimean-Congo hemorrhagic fever (CCHF) is a disease with high fatality. To demonstrate the effectiveness of ribavirin against CCHF. The first group of 21 patients received ribavirin within 4 days of the onset of symptoms (early use of ribavirin, EUR); the second group of 20 patients received ribavirin a parts per thousand yen5 days after the onset of the symptoms of the disease (late use of ribavirin, LUR); and the last group of 11 patients did not receive ribavirin (no use of ribavirin, NUR). At 5-10 days from the onset of symptoms the mean platelet counts of the patients in the EUR group were significantly higher than those of the patients in LUR group, and at 7-9 days, they were significantly higher than that of the patients in the NUR group. The mean aspartate transferase levels in the EUR group were significantly lower than of the NUR group on days 8 and 9, and the mean alanine transferase level was significantly lower on day 8 after the onset of the symptoms. There is a beneficial effect of ribavirin if given at an early phase of the CCHF. We suggest ribavirin use especially in the early phase of the disease.
Keywords: CLINICAL-FEATURES; ORAL RIBAVIRIN; RISK-FACTORS; TURKEY; EFFICACY; OUTBREAK